Determination of Optimal Conditions for Extraction of Alcohol-soluble Eugenol Containing Material from Cloves - Myint, San; Wan Daud, Wan Ramli; Mohamad, Abu Bakar (Universiti Putra Malaysia Press, 1995)
Clove oleoresin (total soluble extract matter) contains an antioxidant compound eugenol. Extraction of eugenol from cloves was studied using 95% ethanol.Trials varying in particle size, extraction temperature, extraction time and solvent to solid ratio were performed and optimal conditions were evaluated. Refractive index was used to monitor the extraction parameters. Extraction patterns of ground clove fractions with size of 500 pm, 355 pm, 250 pm and less than 250 pm with solvent to solid ratio of 4: 1 at room temperature were studied. Agitation was ensured by a reciprocating shaker. Optimal size for the extraction at room temperature was 250 pm. Trials on extraction temperature were varied from 30°C to 70°C with the same solvent to solid ratio for particle size of 250 pm and 355 pm. Optimal tempel-atures for 250 Fll1 and 355 pm were 50°C and 60°C respectively.